O processo de acreditação hospitalar na perspectiva de profissionais de saúde - Bruna Figueiredo Manzo (2009)
In order to reach the highest assistance patterns it was adopted some practices focused on the Hospital Accreditation process. They assert some new demands concerning with behavior changes, the steady staffs mobilization to achieve required goals and purposes besides a permanent and continuous improvement of Health care service. It is a qualitative case study which aimed to analyze the Hospital Accreditation process from a Health care staffs view in a private hospital in Belo Horizonte. The research was done with the Health care staff allocated in three sectors of the hospital (Surgical Block, Progressive Cares Unit and Internment Unit) by semi-structured interviews from September to November, 2008. The data organization and analysis were based on thematic analysis of content. From the data analysis emerged four empirical categories: 1. The accreditation in the Health care staffs view; 2. The implications of the accreditation process for the hospital, patients and health care staff; 3. Aspects which facilitate and make it difficult for the hospital Accreditation; 4. Strategies pointed out by the health care staff in order to seek the maintenance of the Quality Process. From the obtainable results it is noticed that there is no consensus on the health care staffs view concerning to the Accreditation process causing any influence in the adhesion and maintenance of the Quality management process. The majority of the interviewees can visualize the Accreditation process in its technical, processional and operational aspects even if it is not in its totality. However, just some of them could recognize that the quality system also covers important subjective aspects such as individual and social people and institutions values especially the humanization of care. Another important finding is regarding the influences of the management system for the hospital, patients and staff. For the interviewees, the hospital can get lots of benefits with the Accreditation process such as status, reference and profit. For patients, it brings a health care service quality assurance even though they recognize that sometimes the system leads to a distance between them and the health care staff. According to the health care staff, the issue is very divergent without achieving a common sense. Furthermore, it was evident not only the lack of maintenance of the Quality System during all the year but also, the staffs little involvement as difficult parts of the process. The group work was considered the main pillar for the Quality Process as a facilitator of the process. The health care staff also recognized that the great challenge they faced on was the maintenance of the Accreditation Process. Viewed in this context, the staffs continuous qualification was pointed out as the main strategy to seek improvements constantly.